TANTANGAN DAN PELUANG IMPLEMENTASI MERDEKA BELAJAR DI MTS DARUL IHSAN SAMARINDA - Iqbal Alfiandy; Muchammad Eka Mahmud (STKIP Subang, 2025)
This study aims to examine the challenges and opportunities in the implementation of Merdeka Belajar at MTs Darul Ihsan Samarinda. A qualitative approach was employed, with data collected through interviews with the head of the madrasah, the vice principal for curriculum, and teaching staff, as well as observations of the learning process in the classroom and the overall school environment. The results indicate that the implementation of Merdeka Belajar at MTs Darul Ihsan Samarinda has begun through various efforts, such as the application of more active learning approaches, the use of diverse teaching methods, and the strengthening of students’ character development. The identified opportunities include increased teacher creativity in designing learning activities, higher student engagement, and strong institutional support for educational innovation. However, several challenges remain, including uneven understanding among teachers regarding the concepts and technical aspects of Merdeka Belajar, limited supporting facilities and infrastructure, and differences in students’ abilities to adapt to learning models that require greater independence and active participation. Therefore, it can be concluded that the implementation of Merdeka Belajar at MTs Darul Ihsan Samarinda has shown fairly positive progress, but it still requires reinforcement in terms of improving teacher competence, providing adequate facilities, and offering continuous guidance for students. This study is expected to serve as a reference and an evaluation tool for madrasahs in optimizing the implementation of Merdeka Belajar more effectively.